1999
DOI: 10.1177/0093854899026001006
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Depression in Prisoners Using the Beck Depression Inventory

Abstract: As part of the admission process to the North Carolina state prison system, 1,494 prisoners completed the Beck Depression Inventory (BDI). The mean BDI score for this population was 12.57 ( SD=8.51), which corresponds to the “mild depression” range on the instrument. While overall BDI scores for prisoners were elevated relative to general population norms for the test, female inmates, younger prisoners, close custody inmates, and those serving their first period of incarceration produced even higher BDI scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 29 publications
4
67
0
4
Order By: Relevance
“…Internal consistency of the BDI-II ranges from .73 to .92 with a mean of .86; (Beck, Steer, & Garbin, 1988). The BDI-II has been used in previous studies with incarcerated populations (e.g., Boothby & Durham, 1999). In the present study, the alpha reliability for the measure was 0.88.…”
Section: Beck Depression Inventorymentioning
confidence: 60%
“…Internal consistency of the BDI-II ranges from .73 to .92 with a mean of .86; (Beck, Steer, & Garbin, 1988). The BDI-II has been used in previous studies with incarcerated populations (e.g., Boothby & Durham, 1999). In the present study, the alpha reliability for the measure was 0.88.…”
Section: Beck Depression Inventorymentioning
confidence: 60%
“…Given that many offenders exhibit symptoms of depression and associated problems, such as selfharm and suicidal behaviour (Boothby and Durham, 1999;Domalanta et al, 2003;Palmer and Connelly, 2005), establishing norms among adult and adolescent offenders is clinically important. The BDI-II showed a high level of internal consistency, in line with previous studies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The BDI-II (and its predecessor the Beck Depression Inventory) has been used to assess depression in offender samples (Boothby and Durham, 1999;Domalanta et al, 2003;Eidhin et al, 2002;Ivanoff et al, 1992;Palmer and Connelly, 2005). Boothby and Durham (1999) conducted a factor analysis of the BDI with incarcerated prisoner in North America, reporting four factors: cognitive symptoms, vegetative symptoms, emotional symptoms, and feelings of punishment. However, the authors found no studies of psychometric properties or factor structure in offender populations for the BDI-II.…”
Section: Introductionmentioning
confidence: 99%
“…Those adhering to traditional social norms and values have also been found to be more likely to resist assimilation into inmate cultures (Irwin, 1970). Further, research has found differences in prison adjustment through emotions, attitudes and behaviors to be a function of either age (MacKenzie, 1987), gender (MacKenzie et al, 1989;Warren, Hurt, Loper, & Chauhan, 2004), or both (Boothby & Durham, 1999). Finally, MacKenzie, Goodstein, and Blouin (1987) and Reitzel and Harju (2000) reveal the importance of inmates' perceived level (or locus) of control over their environment as an important influence on inmates' prison adjustment.…”
Section: Special Sensitivity To Prison 1093mentioning
confidence: 99%